2006
DOI: 10.1042/bj20060913
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between substrates and the haem-bound nitric oxide of ferric and ferrous bacterial nitric oxide synthases

Abstract: We report here the resonance Raman spectra of the FeIII-NO and FeII-NO complexes of the bacterial NOSs (nitric oxide synthases) from Staphylococcus aureus and Bacillus subtilis. The haem-NO complexes of these bacterial NOSs displayed Fe-N-O frequencies similar to those of the mammalian NOSs, in presence and absence of L-arginine, indicating that haem-bound NO and L-arginine had similar haem environments in bacterial and mammalian NOSs. The only notable difference between the two types of NOS was the lack of ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 52 publications
1
20
0
Order By: Relevance
“…5 B). A very intense line and a shoulder at the same frequencies were observed previously in the low-frequency region of the spectrum of the Fe III NO complex of saNOS and were assigned to the n Fe-NO mode (539 cm À1 ) and d Fe-N-O (553 cm À1 ) mode, respectively, based on the isotope shifts (32). No other heme complex of saNOS is known to display such intense lines at these frequencies (half the intensity of n 8 at 674 cm À1 ).…”
Section: Characterization By Resonance Raman Spectroscopy Of the Intesupporting
confidence: 72%
“…5 B). A very intense line and a shoulder at the same frequencies were observed previously in the low-frequency region of the spectrum of the Fe III NO complex of saNOS and were assigned to the n Fe-NO mode (539 cm À1 ) and d Fe-N-O (553 cm À1 ) mode, respectively, based on the isotope shifts (32). No other heme complex of saNOS is known to display such intense lines at these frequencies (half the intensity of n 8 at 674 cm À1 ).…”
Section: Characterization By Resonance Raman Spectroscopy Of the Intesupporting
confidence: 72%
“…The resonance Raman spectrum of this intermediate acquired 81 ms after mixing confirmed that an Fe III NO complex was not formed, as no ␦ Fe-NO mode at 548 cm Ϫ1 was observed in the low frequency region (Fig. 4, traces E and F) (23,26). An Fe II NO complex, which would be in the six-coordinate and low spin state if NOHA was still bound to saNOS (26), was not formed either because the strong Fe-NO / ␦ Fe-N-O modes expected near 555 cm Ϫ1 were not detected.…”
Section: Resultsmentioning
confidence: 85%
“…Enzyme Preparation-saNOS and bsNOS were expressed in Escherichia coli from the cloned genes and purified as described previously (25,26). Samples were maintained in 40 mM HEPES (pH 7.6), 150 mM NaCl, and 1 mM DL-dithiothreitol.…”
mentioning
confidence: 99%
“…The pull effect engages the distal H-bond network that mediates the two proton transfers required for oxygen activation and, for NOS, L-Arg hydroxylation. The resonance Raman fingerprints of numerous saNOS (39 -41) and bsNOS (42,43) complexes reveal no significant differences in the heme distal environment of bacNOSs and mNOSs (44 -46). Some subtle differences have been observed between the x-ray structures of Fe II NO complexes of bsNOS (47) and neuronal NOS (nNOS) (48,49) in the presence of NOHA and L-Arg, but they should not significantly affect the proton transfer processes.…”
mentioning
confidence: 99%